Serial Microbiota Analysis after Fecal Microbiota Transplantation in a Child with Down's Syndrome - Beurden, Yvette H. van; Meijer, Lisethe; Vermont, Clementien L.; Budding, Andries E.; Mulder, Chris J.J.; Meij, Tim G. de (Journal of Pediatric Infectious Diseases, 2019)
Fecal microbiota transplantation (FMT) is a very effective treatment for recurrent Clostridium difficile infection (CDI) in adults. However, there is a paucity of data on FMT in children and associated microbiome changes in this particular group. We describe a child with Down's syndrome and intracranial malignancy, who received FMT for recurrent CDI. Detailed microbiota analysis before and after FMT, and pre- and post-recurrence, linked to microbial communities in the donor feces showed that the patient developed a unique microbiota profile after FMT which was very stable over time despite CDI recurrence and subsequent fidaxomicin therapy. Bacteroidetes were stably acquired from donor feces, while Firmicutes, Actinobacteria, Fusobacteria, Verrucomicrobia, and Proteobacteria were unique to the patient. The diversity of microbiota of the patient increased from a Shannon diversity index of 2.08 pre-FMT to 3.12 post-FMT. Our findings underscore that patients with Down's syndrome may well tolerate and benefit from FMT even in a severely immunocompromised state.
Keywords: fecal microbiota transplantation; Clostridium difficile infection; Down's syndrome; microbiota analysis; child